Christian Witness to People of African Traditional Religions - Mini-Consultation on Reaching Traditional Religionists (Lausanne Committee for World Evangelization, 1980)
This report, Christian Witness to People of African Traditional Religions, is one of a series of Lausanne Occasional Papers (LOPs) emerging from the historic Consultation on World Evangelization (COWE) held in Pattaya, Thailand, in June 1980. The report was drafted by members of the "Mini-Consultation on Reaching Traditional Religionists," under the chairmanship of Rev. Tite Tienou. The major part of this report went through a draft and a revised draft, which involved all members of the mini-consultation. It was also submitted to a wider "sub-plenary" group for comment, but the responsibility for the final text rests with the mini-consultation and its chairman. The report is released with the prayer and hope that it will stimulate the church and individual members in reaching this large segment of the population.
free